Flag Respect in Indonesia: A Study of Islamic Literature and Legislation in Indonesia - Huda, Bakhrul; Syam, Nur; Safiudin R., Achmad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
The tribute of the flag is routinely debated on social media, with a flag ceremony held on 17 August each year. Such issues appear to be annual discussions, although there are logical reasons for the party to unanimously express respect for the flag. This article was presented to add academic literature to honoring the flag by answering how unquestioned human diversity is in Islamic literature, how the urgency of the flag in Islamic literature, and how urgency honors the flag in the legal state. The method used to answer these questions is a descriptive qualitative research method with a literary study approach. The sources used are secondary data obtained by authors of Verses, Hadith, Classical Islamic literature, legislation, journals, processes, and relevant online news. The result of the discussion was to become sunnatullah of the existence of humans who are of different ethnicities and nations. The flag that represents a nation or a nation exists and is recorded in the history of Islamic literature. The salute of the flag as an expression of gratitude, a love of the fatherland, commemorating the hero's ceremonial service, which proved there is no Shirk word in the anthem, the blessing of ceremony-bearers and the words of prayer recited at the end of the ceremony are acceptable, recommended even (should) on postulate ṣaḥīḥ even above ṣarīḥ. The attitude of the flag in the legislation is in Article 20 PP. No. 40 of 1958 and Article 15 of Law No. 24 of 2009, respect means to uphold the state's identity while also being a form of love and acknowledging the sovereignty and honor towards the state.